Civil conflict and voting behavior: Evidence from Colombia. (November 2018) - Gallego, Jorge
What are the effects of war on political behavior? Colombia is an interesting case in which conflict and elections coexist, and illegal armed groups intentionally affect electoral outcomes. Nonetheless, groups have used different strategies to alter these results. This paper argues that differential effects of violence on electoral outcomes are the result of deliberate strategies followed by illegal groups, which in turn result from military conditions that differ between them. Using panel data from Senate elections from 1994 to 2006 and an instrumental variables approach to address potential endogeneity concerns, this paper shows that guerrilla violence decreases turnout, while paramilitary violence has no effect on participation, but reduces electoral competition and benefits non-traditional third parties. FARC violence is significantly higher during election years, while paramilitary violence is lower. This is consistent with the hypothesis that the guerrillas' strategy is to sabotage elections, while paramilitaries establish alliances with certain candidates.